Social Transformation and Challenges of Traditional Music in the Era of Globalization: A Case Study of Talempong in West Sumatra - Rina Armeniza Aziz; John JOI Ihalauw; Sugiarto Sugiarto (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Traditional music plays a crucial role in local cultural identity, yet faces pressures from globalization, modernization, and urbanization. This article examines the social transformation and sustainability challenges of Talempong, a Minangkabau percussion ensemble in West Sumatra, through a qualitative case study based on ethnographic observation, interviews, and document analysis. Results reveal tonal, technical, and functional hybridization; weakening intergenerational transmission due to urbanization and the erosion of nagari structures; and the commodification of Talempong for tourism and popular entertainment, which opens up economic opportunities while diminishing ritual authenticity. The discussion places these findings within the framework of glocalization, cultural hybridity, and sustainability, concluding that Talempong's survival depends on adaptive, community-based revitalization that balances authenticity with digital innovation, the creative economy, and youth education. Such approaches are essential to ensure that Talempong remains a dynamic cultural practice capable of evolving with social change while preserving its historical significance, symbolic meanings, and Minangkabau cultural identity.